Metode Pembelajaran Pendidikan Kewirausahaan - Natriani Syam; Muhammad Zia- ulHaq; Muhammad Irfan; Romansyah Sahabuddin (DIDAKTIKA, 2024)
Entrepreneurship education is an important field to teach in schools/universities because it can develop personality characteristics needed in the world of work. Apart from that, entrepreneurship education can also introduce the world of entrepreneurship, providing opportunities to create jobs for graduates, so that it can support economic growth and community development. In today's ever-evolving world, a person not only needs to have special knowledge in a particular field, but also must have skills such as creativity, innovation, being able to see opportunities, thinking analytically, and the ability to take risks wisely. Entrepreneurship education helps students to develop these personality characteristics through various activities such as learning such as debriefing, entrepreneurship training, simulations, making business plans, internships, and entrepreneurship practices that involve students in generating ideas, identifying opportunities, solving problems, and making informed decisions wise.